(untitled) (European Journal of Pure and Applied Mathematics, 2017)
Max-stability is the foundation of multivariate extreme values analysis. This paper investigates a asymptotic dependence modeling of max-stable processes both with spatial and temporal variables. SpeciÂ…cally the paper provides new characterizations of extremal distributions via a dependence measure of the stochastic joint behavior at given locality s and date t. The analytical forms of spatio-temporal asymptotic dependence structures are provided for the main bivariate and trivariate models of max-stable processes.